Half-life measurements of highly charged radionuclides - Atanasov, Dinko; Balabanski, D.; Batist, L.; Blaum, Klaus; Bosch, F.; Boutin, D.; Brandau, C.; Dimopoulou, C.; Essel, H. G.; Faestermann, T.; Geissel, H.; Hagmann, S.; et al. (Physica scripta, 2013)
In recent years several measurements of the orbital electron capture half-lives of few-electron ions have been carried out employing the storage ring ESR at GSI. Hydrogen-like and helium-like 140Pr and 142Pm as well as hydrogen-like 122I were studied. Half-lives of the corresponding fully ionized nuclides provide the three-body β+ decay constants.
Gesehen am 27.11.2020